2021
DOI: 10.1002/jbio.202000454
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of perfusion and metabolism in an autism mouse model assessed by diffuse correlation spectroscopy andnear‐infraredspectroscopy

Abstract: There is a need for quantitative biomarkers for early diagnosis of autism.Cerebral blood flow and oxidative metabolism parameters may show superior

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Further, relative differences in tissue dynamics between a normal brain and stroke‐affected regions were observed [18]. Another approach is the combination of NIRS with DCS adopted in this study, as a noninvasive technology for monitoring cerebral blood flow without any contrast enhancer [32, 34]. This method has already been validated for measuring hemodynamic parameters through previously reported experiments [19, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Further, relative differences in tissue dynamics between a normal brain and stroke‐affected regions were observed [18]. Another approach is the combination of NIRS with DCS adopted in this study, as a noninvasive technology for monitoring cerebral blood flow without any contrast enhancer [32, 34]. This method has already been validated for measuring hemodynamic parameters through previously reported experiments [19, 21].…”
Section: Discussionmentioning
confidence: 99%
“…The acquired frames were corrected against the average intensity of 500 background images, where the intensity of the mean of dark background images was subtracted from the signal as dark noise correction before commencing data collection for the experiment, and an area of 200 × 200 pixels of the corrected speckle pattern was used for 1/K 2 s calculation. In our initial experiment, we compared the SCOS results with a lab-standard diffuse correlation spectroscopy system, which was detailed in our previous publication [32]. Briefly, the DCS system consists of a long-coherence (~10 m) laser source (785 nm Crysta-Laser Inc., Reno, NV, USA), eight NIR-optimized single-photon counting modules (SPCM-NIR, Excelitas, Vaudreuil-Dorion, QC, Canada), and an 8-channel auto-correlator board (Correlator.com), of which one channel was used.…”
Section: Resultsmentioning
confidence: 99%
“…DCS has been shown to be a reliable method to obtain CBF contrasts in animals and humans. Rinehart et al found that mice in the autism group had significantly lower CBF compared to control group by using DCS [28]. However, to our best knowledge, DCS…”
Section: Introductionmentioning
confidence: 93%